2012
DOI: 10.1002/elps.201200169
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of resolution increase of free‐flow electrophoresis via simple interval sample injection and separation

Abstract: Interval free-flow zone electrophoresis (FFZE) has been used to suppress sample band broadening greatly hindering the development of free-flow electrophoresis (FFE). However, there has been still no quantitative study on the resolution increase of interval FFZE. Herein, we tried to make a comparison between bandwidths in interval FFZE and continuous one. A commercial dye with methyl green and crystal violet was well chosen to show the bandwidth. The comparative experiments were conducted under the same sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 53 publications
0
20
1
Order By: Relevance
“…For the sake of convenience of mathematic treatment herein, following assumptions were given briefly: (1) uniform mobility of solute; (2) uniform and constant conductance through the whole chamber of FFE; (3) uniform and constant diffusional coefficient among different solutes; (4) uniform flow of background buffer through the whole separation chamber; (5) uniform and constant temperature in whole chamber due to good control of Joule's heat; (6) no convection caused by Joule's heat in FFE chamber. Those assumptions have been used for simple theoretical performance of electrophoresis by numerous scientists .…”
Section: Resultsmentioning
confidence: 99%
“…For the sake of convenience of mathematic treatment herein, following assumptions were given briefly: (1) uniform mobility of solute; (2) uniform and constant conductance through the whole chamber of FFE; (3) uniform and constant diffusional coefficient among different solutes; (4) uniform flow of background buffer through the whole separation chamber; (5) uniform and constant temperature in whole chamber due to good control of Joule's heat; (6) no convection caused by Joule's heat in FFE chamber. Those assumptions have been used for simple theoretical performance of electrophoresis by numerous scientists .…”
Section: Resultsmentioning
confidence: 99%
“…The true benefits of interval FFE were investigated in a quantitative study in 2012. It was demonstrated that FFE separation power could be increased by reducing band broadening caused by the simultaneous effects of electrophoresis and hydrodynamic flow [72]. While interval FFE is an effective way to increase separation power, the platform becomes a combination of discontinuous flow and discontinuous separation.…”
Section: Ffe Separation Efficiencymentioning
confidence: 99%
“…However, this approach suffers from a number of effects that result in band broadening and thus a lower resolution of the FFE separation. Such effects includes diffusional broadening, hydrodynamic broadening, electromigration dispersion, and heat broadening (Shao et al 2012). A number of developments have been made in order to counter these effects, including the use of concentrating modes such as isoelectric focusing or isotachophoresis, operated with pH gradients or steps in the separation buffer, respectively (Hoffstetter-Kuhn et al 1990, Moritz andSimpson 2005).…”
Section: Free Flow Electrophoresismentioning
confidence: 99%